A novel X-linked trichothiodystrophy associated with a nonsense mutation in RNF113A. Issue 4 (22nd January 2015) - Corbett, Mark A; Dudding-Byth, Tracy; Crock, Patricia A; Botta, Elena; Christie, Louise M; Nardo, Tiziana; Caligiuri, Giuseppina; Hobson, Lynne; Boyle, Jackie; Mansour, Albert; Friend, Kathryn L; Crawford, Jo; et al.
Abstract : Background: Trichothiodystrophy (TTD) is a group of rare autosomal recessive disorders that variably affect a wide range of organs derived from the neuroectoderm. The key diagnostic feature is sparse, brittle, sulfur deficient hair that has a 'tiger-tail' banding pattern under polarising light microscopy. Patients and methods: We describe two male cousins affected by TTD associated with microcephaly, profound intellectual disability, sparse brittle hair, aged appearance, short stature, facial dysmorphism, seizures, an immunoglobulin deficiency, multiple endocrine abnormalities, cerebellar hypoplasia and partial absence of the corpus callosum, in the absence of cellular photosensitivity and ichthyosis. Obligate female carriers showed 100% skewed X-chromosome inactivation. Linkage analysis and Sanger sequencing of 737 X-chromosome exons and whole exome sequencing was used to find the responsible gene and mutation. Results: Linkage analysis localised the disease allele to a 7.75 Mb interval from Xq23–q25. We identified a nonsense mutation in the highly conserved RNF113A gene (c.901 C>T, p.Q301*). The mutation segregated with the disease in the family and was not observed in over 100 000 control X chromosomes. The mutation markedly reduced RNF113A protein expression in extracts from lymphoblastoid cell lines derived from the affected individuals. Conclusions: The association of RNF113A mutation with non-photosensitive TTD identifies a new locus for these disorders on the X chromosome. The extended phenotype within this family includes panhypopituitarism, cutis marmorata and congenital short oesophagus.